2011
DOI: 10.1021/ac103301r
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Detection of HER2 Extracellular Domain in the Serum of Breast Cancer Patients by Piezoelectric Microcantilevers

Abstract: Rapid and sensitive detection of serum tumor biomarkers are needed to monitor cancer patients for disease progression. Highly sensitive piezoelectric microcantilever sensors (PEMS) offer an attractive tool for biomarker detection, however their utility in the complex environment encountered in serum has yet to be determined. As a proof of concept, we have functionalized PEMS with antibodies that specifically bind to HER2, a biomarker (antigen) that is commonly overexpressed in the blood of breast cancer patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 33 publications
2
50
0
Order By: Relevance
“…Therefore, the time average of the resonance frequency shifts over the period t = 50 - 60 min at each concentration was obtained to approximate the “equilibrium” resonance frequency shifts, Δf. This method for calculating Δf was described in a previous publication [36]. The obtained Δf were -2200±53, -1082±54, -528±38, -194±42, and -28±15 Hz for 60,000, 6,000, 600, 60, and 6 ng/ml of Her2 in diluted serum, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, the time average of the resonance frequency shifts over the period t = 50 - 60 min at each concentration was obtained to approximate the “equilibrium” resonance frequency shifts, Δf. This method for calculating Δf was described in a previous publication [36]. The obtained Δf were -2200±53, -1082±54, -528±38, -194±42, and -28±15 Hz for 60,000, 6,000, 600, 60, and 6 ng/ml of Her2 in diluted serum, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Detection limit, however, is still an issue and highlights the need for ultrasensitive immunological tests. Loo et al developed a piezoelectric microcantilever sensors (PEMS) with 5 fold higher sensitivity than ELISA and was able to detect HER2 ECD in serum at concentrations below the low end of normal range (2 ng/ml)[79]. A new assay based on linear RNA amplification termed Fluorescent Amplification Catalyzed by T7 RNA polymerase Technology (FACTT) reported even higher sensitivities [80].…”
Section: Developments For Future Serum Her2 Ecd Testmentioning
confidence: 99%
“…The studies have shown that it is overexpressed in approximately 30% of breast cancers, and its presence is associated with a poor prognosis . Recently, it has also been reported that the glycosylated peptides from HER2 have been detected in the serum of breast cancer patients and could be used as promising therapeutic target . PGRMC1 is another important biomarker for breast cancer progression.…”
Section: Current Statusmentioning
confidence: 99%